Enhanced reversibility of the magnetoelastic transition in (Mn, Fe)2(P, Si) alloys via minimizing the transition-induced elastic strain energy. (20th March 2022) - Miao, Xuefei; Gong, Yong; Zhang, Fengqi; You, Yurong; Caron, Luana; Qian, Fengjiao; Guo, Wenhui; Zhang, Yujing; Gong, Yuanyuan; Xu, Feng; van Dijk, Niels; Brück, Ekkes
Highlights: Generalized relationship: hysteresis v.s. transition-induced elastic strain energy. Hysteresis reduced by 91% after replacement of Fe by 4 at.% Mo in (Mn, Fe)2(P, Si). Reversible adiabatic temperature change enhanced by 500 via 4 at.% Mo substitution. Spin-lattice-electron coupling dominate magnetoelastic transition in (Mn, Fe)2(P, Si). Abstract: Magnetocaloric materials undergoing reversible phase transitions are highly desirable for magnetic refrigeration applications. (Mn, Fe)2 (P, Si) alloys exhibit a giant magnetocaloric effect accompanied by a magnetoelastic transition, while the noticeable irreversibility causes drastic degradation of the magnetocaloric properties during consecutive cooling cycles. In the present work, we performed a comprehensive study on the magnetoelastic transition of the (Mn, Fe)2 (P, Si) alloys by high-resolution transmission electron microscopy, in situ field- and temperature-dependent neutron powder diffraction as well as density functional theory calculations (DFT). We found a generalized relationship between the thermal hysteresis and the transition-induced elastic strain energy for the (Mn, Fe)2 (P, Si) family. The thermal hysteresis was greatly reduced from 11 to 1 K by a mere 4 at.% substitution of Fe by Mo in the Mn1.15 Fe0.80 P0.45 Si0.55 alloy. This reduction is found to be due to a strong reduction in the transition-induced elastic strain energy. The significantly enhanced reversibility of the magnetoelastic transition leads to a remarkable improvement of the reversible magnetocaloric properties, compared to the parent alloy. Based on the DFT calculations and the neutron diffraction experiments, we also elucidated the underlying mechanism of the tunable transition temperature for the (Mn, Fe)2 (P, Si) family, which can essentially be attributed to the strong competition between the covalent bonding and the ferromagnetic exchange coupling. The present work provides not only a new strategy to improve the reversibility of a first-order magnetic transition but also essential insight into the electron-spin-lattice coupling in giant magnetocaloric materials. Graphical abstract: Image, graphical abstract